Minimally Invasive Unilateral Laminectomy for Bilateral Decompression - Mobbs, Ralph (JBJS Essent Surg Tech, 2017)
INTRODUCTION: Unilateral laminectomy for bilateral decompression (ULBD) is a recently popularized minimally invasive surgical technique for decompression of the spinal canal. INDICATIONS & CONTRAINDICATIONS: STEP 1: POSITIONING, INCISION, AND INSTRUMENTS REQUIRED: With the patient prone on the spinal table of your choice, use an image intensifier to determine the incision position and then position the retractor of your choice to identify the inferior aspect of the superior lamina. STEP 2: BONE REMOVAL: Begin the laminotomy on the approach side, drilling to identify the ligamentum flavum on the approach side, and remove bone up to the superior attachment of the ligamentum flavum. STEP 3: UNDERCUTTING OF THE SPINOUS PROCESS: To gain access to the contralateral side of the canal for bilateral decompression, remove enough of the spinous process to gain access to the midline and contralateral ligamentum flavum. STEP 4: IDENTIFY THE SUPERIOR ASPECT OF THE LIGAMENTUM ATTACHMENT: The superior aspect of the decompression usually corresponds with the superior ligamentum flavum attachment, except in certain cases such as when a facet joint cyst extends beyond the limits of the ligamentum flavum; removal of the upper limit of the ligamentum flavum provides an important landmark to confirm the superior limit of the decompression. STEP 5: LATERAL RECESS DECOMPRESSION ON THE IPSILATERAL APPROACH SIDE: Detach the ligamentum flavum from the facet joint on the approach side using a combination of angled curets and Kerrison rongeurs; a partial medial facetectomy, or removal of adequate facet hypertrophy, on the approach side is necessary to expose the traversing nerve root. STEP 6: DECOMPRESSION OF THE CONTRALATERAL SIDE OF THE CANAL: Decompression of the thecal sac on the contralateral side of the canal is the potentially dangerous aspect of the procedure, with the highest risk of dural injury and a cerebrospinal fluid leak; thus, create enough room on the ipsilateral side so that instruments can be safely introduced into the canal for the contralateral decompression. STEP 7: HEMOSTASIS: Reducing the paraspinal muscle dissection substantially reduces iatrogenic muscle injury and blood loss, and oozing from the bone removal can be easily controlled with bone wax or a variety of hemostatic agents. STEP 8: CLOSURE: Closure of a unilateral muscle exposure is rapid and the use of wound drainage is very rare, further reducing operative time as well as exposure to complications related to wound drains and subsequent infection risk. RESULTS: One of us (R.M.) and colleagues(5) conducted a prospective randomized trial comparing ULBD with open laminectomy for degenerative lumbar spinal stenosis in 54 patients (27 in each arm of the study) treated from 2007 to 2009. PITFALLS & CHALLENGES: